Masjid dan dakwah : merencanakan, membangun, dan mengelola masjid : mengemas substansi dakwah, upaya pemecahan krisis moral dan spiritual - Nana Rukmana D. W., 1954- (Jakarta : Al-Mawardi Prima, 2002)
Architectural planning and management of mosques as Muslim community centers in Indonesia.
Includes bibliographical references (p. 307-310)
Keywords: Mosques -- Indonesia; Architecture, Islamic -- Indonesia; Mosques as community centers